Atmospheric Muon Charge Ratio Analysis at the INO-ICAL Detector. (1st July 2019) - Singh, Jaydip; Singh, Jyotsna
Abstract : The proposed Iron Calorimeter (ICAL) detector at Indian Neutrino Observatory (INO) will be a large (50 kt) magnetized detector located 1270 m underground at Bodi West Hills in Tamilnadu. ICAL is capable of identifying the charge of the particles. In this paper its potential for the measurement of the muon charge ratio is explored by means of a detailed simulation-based study, first using the CORSIKA code and then comparing it with an analytical model (the pika model). The simulated muon charge ratio is in agreement with the existing experimental observations; its measure can be extended by INO-ICAL up to 10.50 TeV and up to 60 degrees.